Impact of Tumor–Stroma Ratio on the Prognosis of Colorectal Cancer: A Systematic Review - Gao, Jinlai; Shen, Zhangguo; Deng, Zaixing; Mei, Lina (Frontiers in Oncology, 2021)
Background: A reliable and cost-effective prognostic tool for stratification and optimal treatment in patients with colorectal cancer is imperative. The TSR (Tumor stromal ratio) could be a promising predictor for predicting poor prognosis in patients with colorectal cancer. Therefore, we conducted the a systematic review addressing the prognostic utility of TSR in colorectal cancer. Methods: This study was carried out according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guideline. An electronic search was completed using commonly used databases PubMed, CENTRAL, Cochrane Central Register of Controlled Trials, and Google scholar till the last search up to May 30th, 2021. STATA version 13 was used to analyze the data. Results: A total of twelve [(ten for Disease free survival (DFS) and seven studies for overall survival (OS)] involving 5047 patients met the inclusion criteria for the quantitative synthesis in the present study. We observed a significantly higher pooled hazard ratio in patients with low tumor-stromal ratio (TSR)/higher stromal content in stage II CRC, stage III, and mixed CRC patients (HR, 1.51; 95% CI: 1.17 to 1.86), (HR, 1.90; 95% CI: 1.35 to 2.45) and (HR, 1.39; 95% CI: 1.18 to 1.61) respectively for predicting disease-free survival. We observed evidence for the statistically significant prognostic value of high stroma content/low TSR for the prediction of the overall survival (HR, 1.62; 95% CI: 1.27 to 1.97) including all stages of CRC. Conclusion: The results of the current meta-analysis showed that high stroma content/low TSR could be a prognostic factor for the prediction of worse prognosis (Overall survival, disease-free survival) in patients with CRC.